Modelagem dinâmica do cenário florestal em unidades de paisagem do bioma Pampa - Lippert, Diogo Belmonte (2014)
The construction of a computational model to adequately represent the forest dynamics is still a challenge, since a number of elements acts as driving forces in promoting growth and reducing forest in the state of Rio Grande do Sul is complex yet combine these factors and consider their values in quantitative and qualitative terms to analyze their influence this dynamic. This study aims to relate the spatial distribution of environmental factors and socioeconomic factors on forests with a dynamic model and simulate predictions of localization and quantification of forests in the landscape units macrozones Depressão Central, Cuesta do Haedo and Escudo Sul-Rio-Grandense. The methodology consisted in mapping physical and socioeconomic attributes in use mapping and land cover classification using MODIS digital image and the structuring of a simulation model of the application Dinamica EGO. The results show the evolution of the use and land cover as well as the expansion, reduction and forest maintenance between the periods 2000 to 2006 and from 2006 to 2012, in which the expansion was superior to other processes. Through dynamic modeling, simulating for the year 2024, it was concluded that the forest expansion will continue to occur. The forest will occupy second place in land coverage and its concentration is greater during the macrozones Depressão Central and Escudo Sul-Rio-Grandense.